Too old for a life-threatening inherited cardiac condition? The importance of cascade genetic testing - Hrib Luciana Andreea; Hadarag Andra Valeria; Casian Mihnea; Papadakis Michael (Romanian Journal of Cardiology)
CPVT is a rare inherited channelopathy which predisposes patients to malignant ventricular arrhythmias during exercise or stress. Although exceptionally rare, the diagnosis can be made in individuals over 40 years.